Socio‐spatial patterning of off‐sale and on‐sale alcohol outlets in a Texas city. (9th December 2013) - Han, Daikwon; Gorman, Dennis M.
Abstract Introduction and Aims To examine the socio‐spatial patterning of off‐sale and on‐sale alcohol outlets following a policy change that ended prohibition of off‐sale outlets in Lubbock, Texas. Design and Methods The spatial patterning of alcohol outlets by licensing type was examined using the k‐function difference (D statistic) to compare the relative degree of spatial aggregation of the two types of alcohol outlets and by the spatial scan statistic to identify statistically significant geographic clusters of outlets. The sociodemographic characteristics of the areas containing clusters of outlets were compared with the rest of the city. In addition, the socioeconomic characteristics of census block groups with and without existing on‐sale outlets were compared, as were the socioeconomic characteristics of census block groups with and without the newly issued off‐sale licenses. Results The existing on‐sale premises in Lubbock and the newly established off‐sale premises introduced as a result of the 2009 policy change displayed different spatial patterns, with the latter being more spatially dispersed. A large cluster of on‐sale outlets identified in the north‐east of the city was located in a socially and economically disadvantaged area of the city. Discussion and Conclusion The findings support the view that it is important to understand the local context of deprivation within a city when examining the location of alcohol outlets and add to the existing research by drawing attention to the importance of geographic scale in assessing such relationships. [Han D, Gorman DM. Socio-spatial patterning of off-sale and on-sale alcohol outlets in a Texas City. Drug Alcohol Rev 2014;33:152–160]